POLA PERESEPAN OBAT PENYAKIT GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RUMAH SAKIT KRAKATAU MEDIKA IHC KOTA CILEGON TAHUN 2023 - Isti Dwi Pruschia; Dwiyarina Margarisa; Mia Dwi Nirmala (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
The kidneys are vital organs that function to maintain blood balance, prevent the buildup of metabolic waste in the body, stabilize water levels in the body, maintain the electrolytes sodium, potassium and phosphate, and produce hormones and enzymes that regulate blood pressure, making red blood cells. The community population is less concerned about kidney disease, because kidney failure is a significant public health problem. Important organs, such as the kidneys, can die if their health is not taken care of. The prescribing pattern is an illustration of appropriate drug use and an important factor in healing. The aim is to determine the pattern of drug prescribing for chronic kidney failure patients undergoing hemodialysis in hospitals. The method in this research was carried out retrospectively, namely in the form of observational research on events that have occurred from medical records, characteristics including gender, age, type of drug, class and diagnosis and type of complication. There were 50 male patients (54.35%) and 42 patients (45.65%) female. The age groups were 41-59 years old (47.83%), 21-40 years old (13.04%), and 60-70 years old (39.13%). The types of drugs most commonly used were Amlodipine (25.00%) and Bicnat (22.83%). The most widely used drug classes are CCB (25.00%) and Antacids (22.83%). The most common diagnoses and types of complications in chronic kidney failure patients undergoing hemodialysis in hospital are hypertension + chronic kidney stage 5 (40.00%). Men are more susceptible to chronic kidney failure due to poor lifestyle habits and smoking. As we age, kidney function decreases due to a reduction in the number of nephrons. Amlodipine, which is not or slightly dialyzed, remains effective in hemodialysis patients. Bicarbonate (bicnat) is used to increase blood and urine pH and neutralize metabolic acidosis in chronic kidney patients. Calcium Channel Blockers (CCB) help stabilize blood pressure and reduce the burden on the kidneys, important because increased blood pressure can worsen decreased kidney function